2013
DOI: 10.4067/s0034-98872013000200014
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensión arterial en la mujer adulta

Abstract: Hypertension in women

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
4
0
2
Order By: Relevance
“…In the present study, we found that women had a 30.2% higher risk for hypertension (95% CI, 1.054–1.607; P =0.014) than men, which indicated menopausal women had a higher prevalence of hypertension than men as they entered in the middle age. These findings suggest that sex hormones have a prominent role in preventing hypertension 13 for women.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, we found that women had a 30.2% higher risk for hypertension (95% CI, 1.054–1.607; P =0.014) than men, which indicated menopausal women had a higher prevalence of hypertension than men as they entered in the middle age. These findings suggest that sex hormones have a prominent role in preventing hypertension 13 for women.…”
Section: Discussionmentioning
confidence: 75%
“…However, it is important to consider that underreporting of hypertension in women may distort the assessment of inconsistent adherence to antihypertensive treatment. However, evidence indicates that women are at higher risk of developing hypertensive disorders in specific contexts, such as pregnancy and menopause (45)(46)(47). In the Peruvian context, there is no clinical-therapeutic approach tailored to these risks, which could lead to inadequate therapeutic regimens with insufficient antihypertensive medication, exacerbating adverse socioeconomic conditions (48-50).…”
Section: Discussionmentioning
confidence: 99%
“…Independent PCA scores plots revealed at least some clustering of the three thyroid status classifications, and, as observed with CCorA model performed, the SBP, DBP and MAP values were significant contributors to the first PC, whereas only the SBP:DBP ratio significantly contributed to the second. Although essential hypertension is more common, secondary hypertension is increasing and is now prevalent in view of associated disorders, which are more common in females [12]. Furthermore, thyroid disorder is the most common endocrinological disorder, and hypertension is more often observed in thyroid diseases.…”
Section: Discussionmentioning
confidence: 99%